ANALISIS PERKEMBANGAN KEBIJAKAN TEKNOLOGI MENDUKUNG PENDIDIKAN DI INDONESIA DAN MALAYSIA - ANDIKA, WAHYU; Rosdiati Mendrofa; Santi Ervilia; Tri Widianto; Riana Sinaga; Teguh Iman Perdana Surbakt; Ahmad Rifqy Ash-Shiddiqy (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to analyze the development of technology policies that support the education systems in Indonesia and Malaysia. As two Southeast Asian countries actively pursuing educational transformation in the digital era, both face similar challenges such as digital inequality, limited infrastructure, and the need to enhance the digital competence of educators. Employing a literature review method, this research draws upon academic journals, policy documents, government reports, and relevant articles to examine the technological education policies implemented, the challenges encountered, and the positive impacts achieved.Indonesia has introduced the Merdeka Belajar (Freedom to Learn) policy, promoting flexibility in learning through the use of digital technology. In contrast, Malaysia has implemented various initiatives such as the ICT Transformation Plan (Pelan Transformasi ICT KPM), CERDIK, and JENDELA to enhance internet access and strengthen digital infrastructure in education. Both countries have also developed 21st-century competency-based curricula that emphasize digital literacy, creativity, critical thinking, and collaboration.The analysis reveals that the integration of technology in education has led to several positive outcomes, including more effective learning processes, improved educational management efficiency, equitable access to digital education, and enhanced teacher competence. Nevertheless, challenges such as digital divides and infrastructure limitations in rural areas remain significant barriers.This study recommends strengthening cross-sector collaboration, establishing long-term strategic planning, and conducting ongoing evaluations of education technology policies to ensure that digital transformation in education is inclusive, sustainable, and responsive to future demands